Extending the Indication of the Superior Thyroid Artery as a Recipient Vessel for Complex Upper Body Defects. Issue 5 (May 2021) - Ehrl, Denis; Broer, P. Niclas; Ninkovic, Milomir; Giunta, Riccardo E.; Moellhoff, Nicholas
Abstract : Background: Reconstruction of complex chest and upper back defects can pose a challenge to microsurgeons, especially when prior surgery, scarring, tumor resection, or radiotherapy, have caused a shortage of recipient vessels. Although already being a standard approach for head and neck reconstructions, we investigated whether the indication of the superior thyroid artery (STA) as a safe and universal recipient vessel could be extended for reconstruction in aforementioned regions. Methods: Seventeen patients received free myocutaneous vastus lateralis (MVL) muscle flaps for reconstruction of upper body defects (chest n = 11; upper back n = 6). In all cases, the STA was used for microvascular anastomosis because of a lack of standard recipient vessels. A retrospective chart review was performed and the data was screened for patients' demographics, intraoperative and perioperative details, flap survival, surgical complications, and overall long-term outcomes. Patients had a minimum follow-up of 6 months. Results: Defects resulted from infections after cardiac surgery (n = 10), infections after spinal neurosurgery (n = 2) or tumor resection (n = 5). Average defect size measured 144.6 (range, 40–286 cm 2 ; ±67.9 cm 2 ), with a mean size of the MVL free flaps of 266.8 (range, 160–384 cm 2 ; ±69.5 cm 2 ). The flap success rate was 100%, with minor complications in 4 patients. No major complications were observed in any of the patients. Conclusions: The STA is a viable and safe alternative as a recipient vessel for reconstruction of upper body defects, especially when other vessels in proximity to the defect are deprived.